2022
DOI: 10.2174/1389557521666211001122118
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Approach to Potential Anticancer Benzimidazole Derivatives: A Review

Abstract: : Cancer is one of the deadliest diseases in many developed and developing countries. Continuous efforts are required for designing better therapeutic agents for the treatment of cancer with more efficacy, selectivity, and less toxicity. The fused heterocyclic ring system has been identified by several researchers as a privileged structure that can be used as a basis for drug discovery in medicinal chemistry. The hetero-aromatic bicyclic ring system acts as a pharmacophore in a wide range of drugs with therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…According to the recent studies, different benzimidazoles derivatives have multitargeting ability, which makes them a significant anchor for the synthesis of novel anticancer agents (Kumar et al, 2022). Interestingly, previous studies have demonstrated the antiproliferative and apoptotic effects of various types of benzimidazoles on different cancer types such as skin, breast, and blood cancers (Kumar et al, 2022). Due to the structure of benzimidazole, as a privileged structure, they can bind to various kinds of proteins such as enzymes through hydrogen bonds coordinated with metal ions or hydrophobic interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the recent studies, different benzimidazoles derivatives have multitargeting ability, which makes them a significant anchor for the synthesis of novel anticancer agents (Kumar et al, 2022). Interestingly, previous studies have demonstrated the antiproliferative and apoptotic effects of various types of benzimidazoles on different cancer types such as skin, breast, and blood cancers (Kumar et al, 2022). Due to the structure of benzimidazole, as a privileged structure, they can bind to various kinds of proteins such as enzymes through hydrogen bonds coordinated with metal ions or hydrophobic interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the anticancer agents induce apoptosis via triggering the apoptosis intrinsic pathway (Fulda & Debatin, 2006). According to the recent studies, different benzimidazoles derivatives have multi‐targeting ability, which makes them a significant anchor for the synthesis of novel anticancer agents (Kumar et al, 2022). Interestingly, previous studies have demonstrated the antiproliferative and apoptotic effects of various types of benzimidazoles on different cancer types such as skin, breast, and blood cancers (Kumar et al, 2022).…”
Section: Discussionmentioning
confidence: 99%